Decompression Procedure using a Microendoscopic Technique for Thoracic Myelopathy Caused by Ossification of the Ligamentum Flavum - Ikuta, K.; Tarukado, K.; Senba, H.; Kitamura, T.; Komiya, N.; Fukutoku, Y.; Shidahara, S. (min - Minimally Invasive Neurosurgery, 2011)
Microendoscopic discectomy (MED) is one of the minimally invasive endoscopic procedures for treating lumbar disc herniation. The aim of this case report is to describe a patient with thoracic ossification of the ligamentum flavum (OLF) that was completely removed using the microendoscopic technique.We report on a 62-year-old male patient who presented with thoracic myelopathy caused by OLF at the Th11-12. A posterior decompression via spinous process splitting approach using the microendoscopic technique at the Th11-12 was performed. The bilateral ossified ligamentum flavum could be en bloc removed separately. A sufficient decompression of the spinal cord and the spinal canal with no evidence of damage on the paraspinal muscles was demonstrated on magnetic resonance images after surgery. The patient’s neurological symptoms were alleviated at 24 months after surgery. There was no evidence of postoperative instability at the final follow-up.The authors found that the microendoscopic technique could be applied to decompression surgery for thoracic OLF. The procedure could provide a sufficient decompression with minimum damage to the paraspinal muscles. However, the microendoscopic procedure should be indicated only for select thoracic OLF, such as OLF without fusion at the middle of the spinal canal and OLF without dural ossification, because of its technical difficulties.
Keywords: minimal invasive spine surgery; endoscopy; laminectomy; thoracic spine; ossification of ligamentum flavum